Modeling the Significance of Sustainability Orientation on the Sustainability Performance of Micro-Enterprises in an Emerging Economy - Wan Mustapa, Wan Nurulasiah binti; Hayat, Naeem; Fazal, Syed Ali; Al Mamun, Abdullah; Salameh, Anas A.; Zainol, Noor Raihani (Frontiers in Psychology, 2022)
Sustainable enterprises are essential for developing economies' progress and prosperity. Micro-enterprises (MEs) play an important role in creating jobs and actively participating in socio-economic activities. However, little is known about how MEs use internal capabilities to achieve long-term success.The current study explores the influence of the strategic orientations (i.e., sales, consumer, competitive, emotional, business, and networking) instigating the sustainability orientation. The sustainability orientation nurtures the sustainable performance of the MEs. The cross-sectional data collected from the 450 MEs with the structured interviews and samples were randomly selected from the list of MEs registered in seven districts of Kelantan, Malaysia. The collected data was analysed with partial least square structural equation modelling (PLS-SEM). The data analysis discovered that the sale, consumer, competitive, and emotional orientation significantly impact the MEs' sustainable orientation. The business and networking orientations insignificantly facilitate the sustainable orientation among the samples. The MEs' sustainable orientation suggestively influences the sustainable performance among the MEs. Furthermore, the study analysis postulated a significant mediating effect of sustainable orientation among the orientations (sale, consumer, competitive, and emotional) on the MEs' sustainable performance. Our study offers a better understanding of the RBV in the MEs and brings significant empirical evidence to attain sustainable performance with the firm's level orientation for the MEs. The study brings forward the practical implication for business and policymakers that the MEs require internal and external support to align the business and networking orientation to harness the sustainable performance among the MEs. In the end, the study limitations and future research options are highlighted.